Premorbid Psychological Factors Associated with Long-Term Postoperative Headache after Microsurgery in Vestibular Schwannoma—A Retrospective Pilot Study - Thomas, Mareike; Rampp, Stefan; Scheer, Maximilian; Strauss, Christian; Prell, Julian; Schönfeld, Robby; Leplow, Bernd (Brain Sciences, 2023)
Associations between premorbid psychological factors and postoperative headache (POH) after microsurgical treatment via the retrosigmoid approach for vestibular schwannoma (VS) were investigated in this retrospective single-center study. A total of 101 VS patients completed the Rostock headache questionnaire (RoKoKo), the hospital and anxiety scale (HADS-D), and the screening for somatoform disorders (SOMS-2), all of which were used as short self-assessed questionnaires. Fifty-four patients with POH were compared with 47 non-POH patients in terms of premorbid psychological factors, somatization tendencies, and psychological burden using the chi2-test and Mann–Whitney U-test. Regression analyses were conducted to assess the weighted contribution of psychological and procedural factors to POH. In individuals with POH, mental ailments, preexisting headaches, premorbid chronic pain syndromes, and higher somatization tendencies were found to be significantly more common. POH was predicted by the number of premorbid psychosomatic symptoms, preexisting mental ailments, and premorbid chronic pain syndromes. Depression and anxiety were predicted by low emotional stability. Additionally, the number of premorbid psychosomatic symptoms predicted depression, anxiety, and overall psychological burden. It was observed that the reported symptoms of headache might fit into the classification of chronic postsurgical pain (CPSP) rather than being classified as secondary headaches after craniotomy. Premorbid psychological factors were found to play an important role in the emergence of POH in VS, particularly after microsurgery via the retrosigmoid approach. Therefore, it is suggested that psychological screening be incorporated into the treatment process.
CRIS-Team Scopus Importer:2023-09-08
Keywords: microsurgery; postoperative headache; premorbid psychological factors; vestibular schwannoma